International perspectives on knowledge and quality : implications for innovation in teacher education policy and practice - Stolare, Martin; Olin-Scheller, Christina; Gericke, Niklas; Hudson, Brian (London [England] : Bloomsbury Academic, 2022)
"Drawing together an international author team from Australia, Finland, France, Germany, Norway, Sweden and the UK, this book examines how we might democratize and open up access to 'knowledge of the powerful' for all. This book moves beyond the narrow knowledge vs skills debate of the 20th century to interrogate the epistemic quality of education in schools, and is a valuable resource for reflecting on the design and implementation of teacher education. Based on a range of national studies by the Knowledge and Quality across School Subjects and Teacher Education network (KOSS), funded by the Swedish Research Council (2019-22), the chapters explore teachers' powerful professional knowledge and the implications this has for innovation in teacher education, policy and practice in educational settings"
Powerful Professional Knowledge and Innovation in Teacher Education Policy and Practice -- Reinventing Subject Teaching in Integrated Teacher Education Programs in Norway -- Teacher Education and History Teachers' Powerful Professional Knowledge -- Embedding Epistemic Quality in the Pedagogy of Student Geography Teachers -- Epistemic Literacy as an Aim for Religious Education and Implications for Teacher Education -- Investigating Literature as Knowledge in School English -- Transforming Circular Economy Principles into Teachers' Powerful Professional Knowledge -- Teachers as Curriculum Makers for School Mathematics of High Epistemic Quality -- Establishing Links to Specialised Knowledge in Social Studies Teaching -- Supporting Teachers' Professional Development in Social Studies Education -- From a Personal to a Pedagogically Powerful Understanding of School Mathematics -- Implications of Powerful Professional Knowledge for Innovation in Teacher Education Policy and Practice.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Teachers -- Training of -- Cross-cultural studies; Education -- Standards -- Cross-cultural studies; Knowledge, Theory of; Education,Teacher training,Educational strategies & policy; Electronic books